Resistance to woobling of wheels of locomotive from the separate constituents of the dynamic loading. - Довбня, Н.П.; Бондаренко, Л.Н.; Бобырь, Д.В.; Шепотенко, А.П. (Problems of Tribology, 2016)
Resistances to woobling are certain from separate constituents at static load on a wheel, inflexibility of springs both for new and threadbare bracers and rails. It is shown that main loading influencing on resistance to woobling of wheels of diesel engines there are loading from static pressure and unevenness of way.